A usability evaluation of the Google Home with non-native English speakers using the system usability scale. (6th May 2022) - Pyae, Aung
Advancements in multidisciplinary research have made voice user interfaces (VUIs) become a reality in both research and commercialisation. Although the existing research has indicated that VUIs are useful in people's daily lives (e.g., personal assistant), there is limited study on non-native English-speaking users' experiences in using commercial VUIs. Hence, in this study, the Google Home Smart Speaker was evaluated with 34 undergraduate students, who use English as a second language, to investigate its usability and user experiences. The SUS, PSSUQ, heuristics questionnaires, and interview questions were used to evaluate the Google Home's usability. The findings report that the Google Home is user-friendly, usable, and useful for non-native English-speaking users. Considering unsolved usability issues found in this study, some usability guidelines are recommended for the design and implementation of future VUIs. The findings also suggest that the SUS is suitable for the assessment of non-native English speakers' use of VUIs.